A Virtual Crossmatch-based Strategy Facilitates Sharing of Deceased Donor Kidneys for Highly Sensitized Recipients. Issue 6 (June 2020) - Roll, Garrett R.; Webber, Allison B.; Gae, David H.; Laszik, Zoltan; Tavakol, Mehdi; Mayen, Luis; Cunniffe, Kelly; Syed, Shareef; Hirose, Ryutaro; Freise, Chris; Feng, Sandy; Roberts, John P.; et al.
Abstract : Background: It is estimated that 19.2% of kidneys exported for candidates with >98% calculated panel reactive antibodies are transplanted into unintended recipients, most commonly due to positive physical crossmatch (PXM). We describe the application of a virtual crossmatch (VXM) that has resulted in a very low rate of transplantation into unintended recipients. Methods: We performed a retrospective review of kidneys imported to our center to assess the reasons driving late reallocation based on the type of pretransplant crossmatch used for the intended recipient. Results: From December 2014 to October 2017, 254 kidneys were imported based on our assessment of a VXM. Of these, 215 (84.6%) were transplanted without a pretransplant PXM. The remaining 39 (15.4%) recipients required a PXM on admission using a new sample because they did not have an HLA antibody test within the preceding 3 months or because they had a recent blood transfusion. A total of 93% of the imported kidneys were transplanted into intended recipients. There were 18 late reallocations: 9 (3.5%) due to identification of a new recipient medical problem upon admission, 5 (2%) due to suboptimal organ quality on arrival, and only 4 (1.6%) due to a positive PXM or HLA antibody concern. A total of 42% of the recipients of imported kidneys had a 100% calculated panel reactive antibodies. There were no hyperacute rejections and very infrequent acute rejection in the first year suggesting no evidence for immunologic memory response. Conclusions: Seamless sharing is within reach, even when kidneys are shipped long distances for highly sensitized recipients. Late reallocations can be almost entirely avoided with a strategy that relies heavily on VXM.